PENGEMBANGAN SITUS UMKM QUELITA CAKE MENGGUNAKAN METODE USER CENTER DESIGN - Shofiati, Ratna; Shan, Putri; Saputra, Aji; Kresna, I Nyoman; Sari, Syandra; Sugiarto, Dedy; Ariwibowo, Anung Barlianto (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2024)
Many people have felt the utilization of information technology in developing applications for the economic sector. Examples of these business applications are Excel, marketplaces, and website creation. As marketing, many businesses, such as Instagram, TikTok, Facebook, and Twitter, are currently utilizing social media to promote their products. One of the marketing businesses is Quelita Cake. Quelita's line of business is the production of pastries and wet cakes. Quality Cake is a small company that utilizes Instagram social media and orders via WhatsApp. To optimize marketing activities to increase the number of consumers and increase company profits, a site development training was held for employees and owners of Quelita Cake. Site development is carried out by interviewing the owner of Quelita Cake, then making a mockup with Figma; the last stage is developing the site with PHP Laravel. Evaluation by distributing questionnaires was carried out to determine the level of visitor satisfaction with the site. The questionnaire results included that 91.4% of visitors stated that the menus on the site were easy and very easy to access, and 88.5% of visitors stated that they were motivated to buy Quelita Cake products